Active monitoring of adverse reactions following COVID-19 and other vaccinations: a feasibility study as part of the CoVaKo project - Zeschick, Nikoletta; Warkentin, Lisette; Kühlein, Thomas; Steininger, Philipp; Überla, Klaus; Hueber, Susann; Sebastiao, Maria (Pilot and Feasibility Studies, 2022)
Background: The Corona-Vakzin-Konsortium project (CoVaKo) analyses the efficacy and safety of COVID-19 vaccines in a real-world setting, as well as breakthrough infections in Bavaria, Germany. A subproject of CoVaKo aims to identify adverse reactions of the COVID-19 vaccine and compare these to adverse reactions of other vaccines in an online survey. In a preceding feasibility study, the study materials were tested for comprehensibility, visual design, and motivation to participate, as well as for their ability to be implemented and carried out in primary care practices and vaccination centres. Methods: We used a mixed-methods research design. First, three focus groups consisting of general population participants were organised to evaluate the study materials and survey. Second, a test roll-out was conducted in vaccination centres and primary care practices that involved implementing and quantitatively evaluating the online survey. Third, interviews were conducted with participating general practitioners and heads of vaccination centres four weeks after the test roll-out. Results: Parts of the information and registration form proved incomprehensible, specifically regarding the recruitment material and/or online survey. For example, headings were misleading given that, relative to other vaccinations, the COVID-19 vaccination was overemphasised in the title. Participants requested additional information regarding the procedure and completion time. Within 31 days, 2199 participants, who received either a COVID-19 vaccination (99%) or at least one of the control vaccinations (1%), registered for the study. Participants (strongly) agreed that the registration process was easy to understand, that the completion time was reasonable, and that the technical setup was straightforward. Physicians and heads of the vaccination centres perceived the study as easy to integrate into their workflow. The majority expressed willingness to participate in the main study. Conclusions: Our study indicated that identifying and documenting adverse reactions following vaccinations using an online survey is feasible. Testing materials and surveys provided valuable insight, enabling subsequent improvements. Participation from health professionals proved essential in ensuring the practicality of procedures. Lastly, adapting the study’s organisation to external fluctuating structures and requirements confirmed necessary for a successful implementation, especially due to dynamic changes in the nation’s COVID-19 vaccination strategies. Trial registration: The trial was retrospectively registered at the “Deutsches Register Klinischer Studien” (DRKS-ID: DRKS00025881) on Oct 14, 2021.
CRIS-Team Scopus Importer:2022-07-15
Keywords: Adverse reactions; COVID-19; General practitioners; Healthcare staff; Online survey; Vaccination; Vaccination centres